The structure of the roundhouse kick on the example of a European Champion of taekwon-do - Wasik, J. (Archives of Budo, 2010)
The roundhouse kick is a kick most often used in a fight. The tactics of a fight in taekwon-do is to hit a chosen point of the opponent`s body as fast as possible. The efficiency of the impact sometimes depends on the speed of the foot, which is itself influenced by the speed and strength of the attacker and the technique applied to perform the attack. Material & methods: A 17-year-old competitor weighing 75 kilograms and measuring 179 cm with the International Master Class was analyzed. For the purpose of this case study he performed a roundhouse kick. A system of complex analysis of movement called Smart-D, made by the Italian company BTS Spa was used for this research. Results: At the first stage of the movement, the competitor rotates his torso, which is going to give the energy to his leg. At the second stage the leg is straightened in the knee joint until reaching the target. The dynamics of the kick depends on the speed of takeoff of the foot and the speed of the rotation movement of the arms. Duration of the kick comprises the time of foot takeoff, which is influenced by the speed and acceleration of the jump, and the time of raising resulting from the power of raising muscles and the technique of the movement.